Longitudinal Weight Gain and Related Risk Behaviors during the COVID-19 Pandemic in Adults in the US - Bhutani, Surabhi (Nutrients, 2021)
Cross-sectional analyses have shown increased obesogenic behaviors and a potential for weight gain during COVID-19 related peak-lockdown (March–May 2020), but longitudinal data are lacking. This study assessed longitudinal changes in body weight and lifestyle behaviors in the US adults during the pandemic. Methods: We used Qualtrics survey to collect self-reported data on body weight, dietary, physical activity, and psychological variables (n = 727) during the peak-lockdown (April/May) and at post-lockdown (September/October). Peak-lockdown weight data were categorized based on the magnitude of weight gained, maintained, or lost, and behavioral differences were examined between categories at two time points. Results: Body weight increased (+0.62 kg; p < 0.05) at the post-lockdown period. The body mass index also increased (26.38 ± 5.98 kg/m(2) vs. 26.12 ± 5.81 kg/m(2); p < 0.01) at the post-lockdown period vs. peak-lockdown period. Close to 40% of participants reported gaining either 1–4 lbs or >5 lbs of body weight during the peak-lockdown, while 18.2% lost weight. Weight-gainers engaged in riskier dietary behaviors such as frequent ultra-processed food intake (p < 0.01) and snacking (p < 0.001), were less active, and reported high stress and less craving control during peak-lockdown. Of those gaining >5 lbs, 33% continued to gain weight after the lockdown eased, while 28% maintain higher body weight. In weight-gainers, takeout meal frequency increased, and high ultra-processed food intake and stress, and low craving control continued to persist after the lockdown eased. Conclusion: We show that the COVID-19 lockdown periods disrupted weight management among many Americans and that associated health effects are likely to persist.